Participatory analysis of plant resource management on Bohol, Philippines - Acebedo, Venancio Agcaoili; Bates, David (Ann Arbor, MI ProQuest Dissertations & Theses Global, 1999)
"Studies and development work concerned with natural resources tend to focus on the utilization and preservation of the biota, often with little regard for the interests, needs, and aspirations of the people who have a direct and immediate stake in those resources. This study demonstrates how natural resource concerns of people on the island of Bohol, Philippines, and those of researchers were brought together and addressed simultaneously. Using participatory approaches that revealed local perspectives and experiences, insights were gained concerning plant resource management in protected areas, which could be used to enhance plant conservation and ecosystem functions while stabilizing crop yields, increasing income, decreasing risks, and reducing labor requirements in small agricultural systems. The research was conducted in partnership with the residents of Owac and Subayon, Bilar, which lie in the protected zone of the Rajah Sikatuna National Park and the Loboc Watershed Rehabilitation Project. Data collection, management and analysis, undertaken jointly, provide a summary of the biophysical, agricultural, and socio-economic attributes of the study site. Among the innovative approaches were the development of a participatory ethnobotanical survey and the use of a community fair as a venue for sharing local people's knowledge and experiences concerning their plant resources. This study indicates that the progressive alteration of the landscape followed a trajectory of increasing population coupled with diminishing biophysical assets and shifting governmental policies. Land degradation and loss of biodiversity have been general. Linked with the withdrawal of land from agricultural and extractive use, a result of governmental protection edicts and fragmentation of farm holdings through inheritance, food security has become problematical for many families. As a consequence, farmers are entering a new phase of land use management that further diversifies their production and land use strategies. Agroforestry, practiced at the farm and community levels, reflects a trend away from simple dominance of annual field crops. Through diversified plot and farm plantings, farmers seek to improve their agroecosystems and provide increased food security and income options. This movement is in keeping with those hypothesized for stressed agricultural environments although the extent of implementation is influenced by the size and the quality of land holding and tenancy status of occupants. Participatory analyses of the current biophysical and socio-economic conditions served to focus resident attention on the underlying nature of the problems and issues affecting their lives, thereby serving to identifying changes, which, if implemented, would enhance both the conservation objectives of the protected areas and the standard of living of local residents."--Abstract.
Thesis (PhD)--Cornell University, 1999.
Includes bibliographical references (leaves 366-373)
Keywords: Electronic books; Plant resource allocation -- Citizen participation -- Philippines -- Bohol; Plant ecophysiology -- Philippines -- Bohol; Political participation